Epidemiology of Autoimmune Hepatitis (AIH) in the United States Between 2014 and 2019: A Population-based National Study. Issue 10 (November 2021) - Tunio, Nahel A.; Mansoor, Emad; Sheriff, Mohammed Z.; Cooper, Gregory S.; Sclair, Seth N.; Cohen, Stanley M.
Abstract : Background and Aims: Autoimmune hepatitis (AIH) is a chronic, inflammatory disease of the liver with increasing prevalence. However, limited epidemiological data exist for the prevalence of AIH in the United States. We used a large database to describe the prevalence of AIH in the United States and the autoimmune diseases associated with it. Approach and Results: Data was collected from a commercial database (Explorys Inc., Cleveland, OH), an aggregate of Electronic Health Record data from 26 major integrated health care systems in the United States. We identified a cohort of patients with a diagnosis of AIH from April 2014 to April 2019 based on a Systemized Nomenclature of Medicine—Clinical Terms and calculated the prevalence of AIH. Of the 37, 161, 280 individuals active in the database from April 2014 to 2019, we identified 11, 600 individuals with a diagnosis of AIH with an overall prevalence rate of 31.2/100, 000. The prevalence of AIH was increased in females compared with males [odds ratio (OR)=3.21, P <0.0001], elderly (aged above 65 y) compared with adults (aged 18 to 65 y) and children (aged below 18 y) (OR=2.51, P <0.0001) and whites compared with African Americans, Asians, and Hispanics (OR=1.12, P <0.0001). Moreover, patients with AIH were more likely to have Sjögren syndrome, systemic lupus erythematosus, ulcerative colitis, celiac disease, rheumatoid arthritis, Crohn's disease, and autoimmune thyroiditis as compared with patients without AIH. Conclusions: We found that the estimated prevalence of AIH in the United States is 31.2/100, 000, which is comparable to the reported prevalence of AIH in Europe. We confirmed that AIH has a strong association with other autoimmune diseases studied in the literature.